The influence of pitch and birefringence on nematicon propagation at the disclination lines in chiral nematic liquid crystals - Kwaśny, Michał; Klus, Bartłomiej; Laudyn, Urszula Anna (Photonics Letters of Poland, 2014)
In this work we study the influence of pitch and birefringence on nematicon propagation at the disclination lines in a wedge shaped planarly oriented sample. We demonstrate that changing the structure parameters can be employed for efficient bending of the soliton trajectory, as a result of reflection. Full Text: PDF References Spatial Solitons, ed. S. Trillo, W. Torruellas (Berlin, Spriger Verlang, 2001) G. Assanto, M. A. Karpierz, "Nematicons: self-localised beams in nematic liquid crystals", Liq. Cryst. 36, 1161 (2009). CrossRef G. Assanto, Nematicons: Spatial Optical Solitons in Nematic Liquid Crystals, (John Willey& Sons 2012). CrossRef M. Peccianti, G. Assanto, A. De Luca, C. Umeton, I. C. Khoo, "Electrically assisted self-confinement and waveguiding in planar nematic liquid crystal cells", Appl. Phys. Lett. 77, 7 (2000). CrossRef M. A. Karpierz, M. Sierakowski, M. Swillo, and T. Wolinski, "Self Focusing in Liquid Crystalline Waveguides", Mol. Cryst. Liq. Cryst. 320, 157 (1998). CrossRef U. A. Laudyn, M. Kwasny, M. A. Karpierz, "Nematicons in chiral nematic liquid crystals", Appl. Phys. Lett. 94, 091110 (2009). CrossRef U. A. Laudyn, P. S. Jung, K. B. Zegadło, M. A. Karpierz and G. Assanto, "Power-induced evolution and increased dimensionality of nonlinear modes in reorientational soft matter", Opt. Letters 39, 6399 (2014) CrossRef U. A. Laudyn, M. A. Karpierz, "Nematicons deflection through interaction with disclination lines in chiral nematic liquid crystals", Appl. Phys. Lett.103 221104 (2013) CrossRef M. Kwaśny, U. Laudyn, K. Rutkowska, M. Karpierz J. of Nonl. Opt. Phys.&Mat. 23, 1450042 (2014) M. Peccianti, C. Conti, G. Assanto, A. De Luca, C. Umeton, "All-optical switching and logic gating with spatial solitons in liquid crystals", Appl. Phys. Lett. 81, 3335 (2002). CrossRef S. Serak, N.V. Tabiryan, M. Peccianti, G. Assanto, "Spatial soliton all-optical logic gates", IEEE Photon. Technol. Lett. 18 (12), 1287 (2006). CrossRef A. Fratalocchi, A. Piccardi, M. Peccianti, G. Assanto, "Nonlinearly controlled angular momentum of soliton clusters", Opt. Letters 32, 1447 (2007). CrossRef H. S. Kitzerrow, Ch. Bar, "Chirality in Liquid Crystals", Springer 2001, New York CrossRef P. Oswald, P. Pieranski, "Nematic and Cholesteric Liquid Crystals: Concepts and Physical Properties Illustrated by Experiments", Taylor & Francis 2005 CrossRef M. Peccianti, A. Dyadyusha, M. Kaczmarek, G. Assanto, Nature Physics 2, 737 (2006). CrossRef M. Peccianti, G. Assanto, A. Dyayusha, M. Kaczmarek, "Nonlinear shift of spatial solitons at a graded dielectric interface", Opt. Letters 32, 271 (2007). CrossRef 1110 nematic mixture was synthesized by Prof. R. Dabrowski at Military University of Technology in Warsaw M. Kwasny, U. A. Laudyn, F. A. Sala, A. Alberucci, M. A. Karpierz and G. Assanto, "Self-guided beams in low-birefringence nematic liquid crystals", Phys. Rev. A 86, 013824 (2012) CrossRef B. Klus, U. A. Laudyn, M. A. Karpierz, B. Sahraoui, "All-optical measurement of elastic constants in nematic liquid crystals", Opt. Express 22, 30257 (2014) CrossRef